Fracture mechanics and reliability of rupture of cast iron rotating disc - Jasim, Haider Hadi (Nahrain University College of Engineering Journal, 2009)
In this paper, the crack propagation in opening mode (Mode I) for three kinds of cast iron rotating disc: Flake graphite cast iron disc, Compacted Vermicular cast iron disc, and Spheroidal graphite cast iron disc are analysed by using Boundary Element Method (BEM) and Finite Element Method (FEM). Weibull uniaxialand multi-axial distribution function is developed and applied to evaluate the reliability of the fracture strength of rotating cast iron disc have inner surface crack. As a result the stress intensity factor (KI) for Flake graphite disc (FGD) is smallest, while (KI) for Spheroidal graphite disc (SGD) was the larger, the value of(KI) for Compacted Vermicular disc (CVD) has intermediate between the two cast iron discs. It is found that there is a convergence between results obtained from uni-axial and multi-axial distribution function, but multi-axial distribution function give high values compared to uni-axial distribution function